Advances in the Understanding of Sress Urinary Incontinence and the Promise of Stem-Cell Therapy - Furuta, Akira (MedReviews, LLC, 2007)
The middle urethra and external urethral sphincter are the focus in management of stress urinary incontinence, and recent cellular-therapy research suggests a new paradigm in treatment. Cell-based therapies are most often described as using autologous multipotent stem cells procured from bone marrow in procedures that may be painful, require anesthesia, and yield low numbers of mesenchymal stem cells upon processing. In contrast, muscleand adipose-derived stem cells can be obtained easily in large quantities under local anesthesia. Instead of lifting the urethra with a sling or bulking up the urethral sphincter with collagen, we now have the potential to restore function with the use of autologous stem cells.